Online simulation to monitor multiphase flow using laser source as transmitter - Naizatul Shima, Mohd Fadzil; Ruzairi, Abdul Rahim; Juliza, Jamaludin; Mohd Hafiz, Fazalul Rahiman; Siti Zarina, Muji; Yasmin, Abdul Wahab (Elsevier, 2021)
This research presents an application of optical tomography for the detection of gas bubbles flowing in a liquid medium. In order to visualise the material inside the pipeline, parallel beam projection had been selected. However, while producing the image, some constraints such as diffraction and reflection in liquid medium will happen, where it will affect the flow accuracy of the result. Therefore, a laser source is used to produce a better image resolution. The column is exposed to a homogeneous light beam and then the ray is detected with the use of optical wave guided detectors. By using parallel projection for 44 laser transmitters and photodiode receivers at the cross-sectional boundary, the existence of bubbles inside a vertical column pipeline is determined. The voltage drop at the sensor directly shows the existence of bubbles between the transmitter and receiver. Linear Back-projection (LBP) is the algorithm that is used to reconstruct the image in real-time. In conclusion, the technique of using parallel beam projection with a laser source can improve the image quality in liquid phase and enables the percentage size of bubbles to be determined.